BigTech in Financial Services : Regulatory Approaches and Architecture - Bains, Parma; Sugimoto, Nobuyasu; Wilson, Christopher (Washington, D.C. : International Monetary Fund, 2022)
BigTech firms are gradually entering the financial sector and becoming important service providers, particularly in emerging markets. BigTechs have entered financial services using platform-based technology to facilitate payments and more recently expanded into other areas, such as lending, asset management, and insurance services. They accumulate data from their nonfinancial and financial activities and draw on consumer data held in different parts of their business (such as via social media). BigTechs are applying new approaches to existing financial services products and services such as underwriting using big data and are also applying machine learning for their key business decisions, such as pricing and risk management across multiple financial sectors. Incumbent financial firms have also increased their reliance on BigTech firms to host core IT systems (for example, cloud-based services, which have the potential to improve efficiency and security). This rapid and significant expansion of BigTechs in financial services and their interconnectedness with financial service firms are potentially creating new channels of systemic risks. To achieve effective implementation and multiple objectives of financial regulation and supervision, a hybrid approach, combining a mix of entity- and activity-based approaches, is needed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Financial Institutions and Services; Foreign Exchange; Informal Economy; Underground Econom